Achilles in love intertextual studies - Fantuzzi, Marco 1957- (Oxford University Press, 2012)
Tracing the escapades of Achilles' erotic history - whether in same-sex or opposite-sex relationships - this book explains how these relationships were developed and revealed, or elided and concealed, in the writing and visual arts following Homer
Includes bibliographical references and index
Keywords: Homer / Iliad; Achilleus -- Fiktive Gestalt; Achilles (Greek mythology) in literature; Achilles (Greek mythology); Sex in literature; Latein; Kunst; Griechisch; Rezeption; Literatur